Religious FatwÄ and Human Security: Managing Public Health through the Lens of Islamic Jurisprudence in Indonesia and Saudi Arabia - Khairul Hamim; Lalu Supriadi Bin Mujib; Ahmad Muhasim (UIN Sunan Gunung Djati, 2024)
This study examines the authorisation of religion in handling COVID-19 through religious fatwÄ issued by the Indonesian Ulema Council, popularly known as the Majelis Ulamaâ€™ Indonesia (MUI), and the Council of Senior Scholars of Saudi Arabia (CSS). The objectives of this study are threefold: firstly, to analyse the methodological formulation of MUI and CSS fatwÄ regarding COVID-19 handling; secondly, to identify the factors underlying the issuance of these fatwÄ; and thirdly, to assess the impact of MUI and CSS fatwÄ on COVID-19 handling. Using a qualitative descriptive research method and conducting a case study of the MUI and CSS fatwÄ institutions, it was found that the methodological basis of the MUI and CSS fatwÄ on COVID-19 includes sources from the Qurâ€™an, hadith, ijmÄâ€™ (consensus), and qiyas (analogy), as well as maqÄá¹£Ä«d sharÄ«â€™ah. Referring to maqÄá¹£Ä«d sharÄ«â€™ah considerations, two priority dimensions emerge as factors in the issuance of MUI and CSS fatwÄ: á¸¥ifáº“ al-dÄ«n (preservation of religion) and á¸¥ifáº“ al-nafs (preservation of life). This study also highlights the significant impact of MUI and CSS fatwÄ on COVID-19 handling. In this context, fatwÄ play a role as part of prevention strategies due to their strong theological influence and effective enforcement of policy implementation. This fatwÄ is especially pertinent given the roles of MUI and CSS, which, from the early stages of the COVID-19 pandemic, have contributed to supporting government policies through the fatwÄ they issued. However, differences exist. MUI fatwÄ tend to be recommendations and appeals, often disregarded by the public as they lack legal sanctions for non-compliance. However, fatwÄ issued by CSS possess absolute authority. This study contributes to a deeper understanding of how religious authorization can support public health policies during a pandemic. Additionally, it offers insights for enhancing the effectiveness of fatwÄ in the context of future health crises.